Rapid and specific detection of Enterococcus faecalis with a visualized isothermal amplification method - Zhu, Bo; Hu, Juan; Li, Xuelian; Li, Xiaomin; Wang, Lei; Fan, Shihui; Jin, Xin; Wang, Kun; Zhao, Weiguo; Zhu, Wenjun; Chen, Cheng; Wang, Zilu; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Enterococcus faecalis is a serious problem for hospitals and can spread from patient to patient. Most of the current detection methods are associated with limitations associated with the need for trained personnel; they are also time-consuming. Thus, it is necessary to develop rapid and accurate detection methods to control the spread of E. faecalis. In this study, we developed a rapid and accurate detection method for E. faecalis using recombinase polymerase amplification (RPA) combined with a lateral flow strip (LFS). This method could be completed in approximately 35 min at 37°C. The limit of detection was 10 CFU, irrespective of whether the templates were pure or complex. This method also showed good specificity and compatibility. In total, 278 clinical samples were detected using the RPA-LFS method; the detection accuracy was equal to that of the conventional qPCR method. This visualized isothermal amplification method could be used for the future on-site detection of E. faecalis.